Observations on changes in ventricular repolarization following four weeks of exercise training in chronic heart failure patients. (1st November 2020) - Caru, Maxime; Gravel, Hugo; Pathak, Atul; Bousquet, Marc; Galinier, Michel; Jacquemet, Vincent; Curnier, Daniel
Abstract: Objective: The aim of this study was to investigate the effects of exercise training on ventricular repolarization dynamicity and heart rate variability in chronic heart failure patients. Design: A total of 22 chronic heart failure patients with reduced ejection fraction in sinus rhythm were included in the study. The patients were in NYHA classes II–III with an ejection fraction of 29.7 ± 7.7%. Before and after 4 weeks of aerobic exercise training, all patients performed a cardiopulmonary exercise test, a standard twelve-lead electrocardiogram and a 24 h Holter recording from which heart rate variability and ventricular repolarization dynamicity were assessed. Results: We observed a significant decrease of QTpeak ( p < .001) and QTend ( p < .001) at RR intervals ranging from 600 to 1000 ms on 24 h QT/RR regressions after 4 weeks of exercise training. Our analyses revealed that short-term exercise training induced significant changes in the frequency and time domain HRV parameters on an overall time-period of 24 h. Conclusion: Four weeks of exercise training induced significant changes in ventricular repolarization dynamicity in chronic heart failure patients. In addition, short-term exercise training was enough to improve patients' heart rate variability.